The double edge sword of John Henryism: Impact on patients' health in the People's Republic of China. (November 2020) - Vargas, Emily A; Li, Yidi; Mahalingham, Ramaswami; Hui, Pan; Liu, Grace; Lapedis, Marissa; Liu, J. Rebecca
The People's Republic of China has experienced extraordinary economic growth, which is associated with increases in chronic health stressors. We examined the impact of John Henryism—a coping mechanism—on various health indicators in a sample of patients ( n  = 642) in China. John Henryism significantly related to increased medical adherence( B = . 03, p < . 001 ) and health-promotional behaviors( B = . 02, p < . 001 ) . John Henryism predicted several indicators of psychological health through social support. John Henryism was also related to increased alcoholism( B = . 04, p < . 05 ) . The findings highlight the complexity and paradoxical implications of John Henryism on health. Implications are discussed in relation to China's epidemiological and age demographic shifts.